From Theory to Practice: The Process of Participatory Theatre in Community Development - Asante, Evans (Journal of Social Science Studies, 2022)
A major concern in community development is the application of various theories, practices, and models that are relevant to the development agenda of the selected community. Participatory theatre practice has been identified as one of such models linking theory and practice in a community development process. Students undergoing training in participatory theatre and community development are introduced to several theories and concepts whose application in the field of work may be quite different from the classroom experience. This paper explores pertinent participatory theatre theories, concepts, and ideals and how they can be effectively put to use at the communal level to achieve an expected outcome. The paper aims to present an easy practical approach to participatory theatre practice in community development.